Knowledge, attitude, and practices of veterinarians towards canine vector-borne pathogens in Sri Lanka. - Ushani Atapattu; Vito Colella; Rebecca J Traub; Anke Wiethoelter (Public Library of Science (PLoS), 2024)
Canine vector-borne pathogens (CVBP) have a worldwide distribution and show a high prevalence in tropical countries such as Sri Lanka. Some CVBP are zoonotic, with dogs identified as reservoir hosts for human subcutaneous dirofilariasis and potentially for spotted fever rickettsioses and re-emergent brugian filariasis in Sri Lanka, making these pathogens emerging public health issues in the country. Veterinarians are crucial in monitoring, preventing, and controlling these pathogens in dogs. Therefore, it is imperative to understand veterinarians' knowledge, attitude, and practices (KAP) regarding CVBP to mitigate their impact. A survey was designed and administered electronically to veterinarians residing and practising in Sri Lanka. Responses were evaluated using descriptive, univariable, and multivariable analyses to investigate associations between demographic factors, knowledge, attitude, and practices related to CVBP. Out of the 170 participating veterinarians, nearly 70% had moderate or high knowledge. However, the awareness of zoonotic pathogens, Brugia spp. (16%) and Rickettsia conorii (18%), was low, and a considerable number of veterinarians were unaware of the zoonotic nature of Dirofilaria repens. Based on multivariable analysis adjusting for experience and self-rated knowledge, new graduates had higher odds of knowledge compared to experienced veterinarians (OR 5.7, 95% CI 1.7-23, p = 0.028). Questions assessing the attitude towards CVBP indicated that most participating veterinarians comprehend and agree with their importance. Nearly all participants agreed that ectoparasite control is the best option to prevent CVBP infections (91%, 153/167) and that for effective treatment of CVBP, a definitive diagnosis is required (81%, 135/167). However, veterinarians recommended suboptimal treatments for some CVBP, like Babesia gibsoni. Better practices were associated with being a companion animal practitioner (OR 2.4, 95% CI 1.1-5.7, p = 0.032) and having a low to moderate canine caseload (OR 3.6, 95% CI 1.3-10.4, p = 0.038). Limited knowledge of zoonotic CVBP among veterinarians, along with suboptimal treatment, might contribute to dogs acting as reservoirs and high prevalence of these pathogens in Sri Lanka. Therefore, continued veterinary education is recommended to improve knowledge and practices, which in turn will help to improve the diagnosis, treatment, and control of these infections in Sri Lanka to ensure the well-being of dogs and humans.